Courageous vulnerability : ethics and knowledge in Proust, Bergson, Marcel, and James - Slegers, Rosa. (Studies in Contemporary Phenomenology, 2010)
This work develops the ethical attitude of courageous vulnerability through the integration of Marcel Proust's novel In Search of Lost Time and the philosophies of Henri Bergson, William James, and Gabriel Marcel. Central to the discussion is the phenomenon of involuntary memory, taken from common experience but "discovered" and made visible by Proust. Through the connection between a variety of themes from both Continental and American schools of thought such as Bergson's phenomenological account of the artist, James' "will to believe," and Marcel's "creative fidelity," the courageously vulnerable individual is shown to take seriously the ethical implications of the knowledge gained from involuntary memories and similar "privileged moments," and do justice to the "something more" which, though part of our experience of ourselves and others, escapes rigid philosophical analysis.